Environmental impacts of hydraulic fracturing - Spellman, Frank R. (CRC Press, 2013)
"Hydraulic fracturing is a well stimulation process used to maximize the extraction of hard-to-reach underground resources. While hydraulic fracturing allows access to previously unobtainable energy supplies, the technology can cause serious damage to environmental media. Public concerns have focused on the impacts of the process used during natural gas production from shale and coalbed methane formations. This book discusses the pros and cons of hydraulic fracturing in a balanced manner. It emphasizes the need for the mining of natural gas to provide future clean energy supplies but also stresses the need for close monitoring of the process, chemicals, and fate of waste products"-- Provided by publisher.
Keywords: Hydraulic fracturing -- Environmental aspects.; elektronické knihy; electronic books